Intra-body temperature monitoring using a biofeedback solution - Caldeira, J.M.L.P. (2011)
“Copyright © [2010] IEEE. Reprinted from 2nd International Conference on eHealth, Telemedicine, and Social Medicine . ISBN: 978-0-7695-3950-8. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”